Тhe interdependence of humanity with the fairy in the mythical space and its reflection in the artistic literature - Aimukhambet, Ж.Ә. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The object of the study of the article is the motifs of the character of the mythical era, the connection of characters similar to fairies with humanity. The images of the fairies in the national worldview were compared with images in world myths such as the elf, nymph, sidah and others, their relationship to human fate was studied. The emphasis is on myths about fairies as a source of folklore and become a traditional motif. Аlso, characters with an amazing destiny and their connection with the mysterious world are found not only in folklore, and examples are given of what in genres of fiction also takes place. The article says that the motifs about fairies are not only the basis of the epics, but also the constant motif of fairy tales and legends. Also, considered characters who left the human world and stayed to live there. At the end of these studies, concluded that the fairies help humanity achieve goal.